2013
DOI: 10.1016/j.tvjl.2012.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between airborne detection of influenza A virus and the number of infected pigs

Abstract: Influenza A virus infects a wide range of species including both birds and mammals (including humans). One of the key routes by which the virus can infect populations of animals is by aerosol transmission. This study explored the relationship between number of infected pigs and the probability of detecting influenza virus RNA in bioaerosols through the course of an acute infection. Bioaerosols were collected using a cyclonic collector in two groups of 7 week-old pigs that were experimentally infected by exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…Influenza virus aerosols could generate during the course of an acute infection to pigs and temporal dynamics of this virus was closely associated with nasal shedding of infected pigs [19]. Influenza viruses could transmit in mammals and humans by aerosols, and healthcare professionals were easily infected within 1.829 m away from patients who released airborne influenza virus into the air by breathing, coughing and sneezing [5,6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus aerosols could generate during the course of an acute infection to pigs and temporal dynamics of this virus was closely associated with nasal shedding of infected pigs [19]. Influenza viruses could transmit in mammals and humans by aerosols, and healthcare professionals were easily infected within 1.829 m away from patients who released airborne influenza virus into the air by breathing, coughing and sneezing [5,6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Results of another field study showed that confined places are more likely to increase aerosol transmission. In contrast, no viral particles were identified outside of the barn, which was attributed to the distribution of particles in a more open space (Corzo, Culhane, et al., ; Corzo, Romagosa, et al., ); however, no association was made with microclimate findings.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies conducted under experimental conditions in mechanically controlled ventilated building showed that the detection of influenza in aerosol was associated to the number of animal shedding at a specific point in time (Corzo, Culhane, et al., ; Corzo, Romagosa, et al., ), although no attempt was made to correlate this finding to the microclimate conditions. Results of another field study showed that confined places are more likely to increase aerosol transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha estimado matemáticamente que el riesgo de transmisión de las partículas en suspensión se eleva exponencialmente con el aumento del número de cerdos que comparten el mismo espacio 23 . Dado que las partículas en suspensión pueden llevar agentes infecciosos, la probabilidad de transmisión por el aire de patógenos entre los cerdos infectados y susceptibles aumenta en los galpones que albergan un gran número de cerdos 2 , que a su vez puede aumentar la propagación de la enfermedad por el contacto de los hocicos de los animales.…”
Section: Medicina Veterinaria Y Zootecniaunclassified